Black-or-White of Online Lending in Indonesia: Conventional Platform or Sharia Scheme (A Netnography Study) - Qadri, Resi Ariyasa; Nabilah, Iffah; Ambarwati, Ria Dewi (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
The numbers of Islamic fintech online loans providers continue to grow during the Covid-19 outbreak. The goal of this research is to look into Islamic fintech-based online loan transactions from an Islamic law and accounting perspective. This study used the interpretive netnography approach, with documentation technique serving as the data collection method, and explanation building tact as the data analysis method. This study found that the use of conventional online loan schemes was having negative consequences, such as an increase in occurrences of despair and suicide among borrowers. Sharia fintech, through its profitless online lending scheme, may reduce the bad effects of the conventional scheme. From the praxis perspective, this research aids to raise public knowledge on avoiding the use of unlawful conventional online loan mechanism. In the future, this research is expected to improve the development of online loans and Islamic fintech research. Keywords : Islamic fintech, netnography, accountability, p2p lending, sharia financial accounting